Synthesis of Metal Oxide Nanoparticles of Nickel(II), Vanadium(V) and Potentiometric Determination of the Stability Constants of Their Complexes with Histidine and Glutamine at Different Temperatures in Aqueous Solutions - Ghiamati, Ebrahim; Lashkari, Maryam; Hasheminia, Monavar (Asian Journal of Chemistry, 2012)
In this research, the stability constants of complexes of L-histidine and glutamine with metal ions and nanoparticles of nickel(II) and vanadium(V) at four different temperatures of 25, 30, 35 and 40 ºC using Bjerrum procedure were determined potentiometrically. In generating the data, GRC Beta software, which is an improved version of BEST routine and developed in our laboratory was used. The parameters affecting the stability constants and behaviour of nanopartiocles with respect to corresponding bulk metallic ions have been discussed. Furthermore, thermodynamics parameters i.e., DH, DS, DG for the complexes were also evaluated.